MANAJEMEN PENERAPAN METODE DISKUSI DALAM MENINGKATKAN KEAKTIFAN SISWA DI SMPN 3 SUBANG - Miftah Zaelani Miftah; Idris Hariri; Martalena; Dessy Prasetia Ningsih (STKIP Subang, 2026)
This study aims to analyze the management of discussion method implementation in improving student activeness at SMPN 3 Subang. The study focuses on planning, organizing, implementing, monitoring, and evaluating the discussion method as well as its impact on students' activeness. This research employed a qualitative approach with a case study method. Data were collected through observations, in-depth interviews, and document analysis. The research participants consisted of the principal, vice principal for curriculum affairs, subject teachers, and students involved in the learning process. Data were analyzed using the Miles, Huberman, and Saldana interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the management of discussion method implementation at SMPN 3 Subang has been systematically carried out through lesson planning, group organization, structured discussion activities, and continuous evaluation. The implementation of the discussion method positively affects students' activeness, as indicated by increased courage to ask questions, express opinions, participate in discussions, collaborate with peers, and interact with teachers. The challenges encountered include students' lack of self-confidence and limited instructional time; however, these obstacles can be addressed through motivation, heterogeneous group formation, and effective classroom management. Therefore, the management of discussion method implementation is proven to be effective in creating active, collaborative, and student-centered learning.